Repair of Complete Atrioventricular Septal Defects With Decellularized Extracellular Matrix: Initial and Midterm Outcomes. (May 2017) - Ashfaq, Adeel; Brown, Tyler; Reemtsen, Brian
Objective: Since April 2010, our institution has repaired complete atrioventricular septal defects (CAVSDs) with a two-patch technique utilizing CorMatrix extracellular material. This material is potentially an attractive patch because of its theorized eventual integration with the host tissue. We sought to analyze initial outcomes of CAVSD repair with CorMatrix. Methods: Data were collected on consecutive pediatric (age <18) patients receiving two-patch CAVSD repairs with CorMatrix at a single institution from April 2010 to July 2014. Baseline and perioperative characteristics were evaluated. Echocardiograms were evaluated in both the immediate postoperative period and the most recent postoperative follow-up. Variables analyzed included left AV valve performance, residual shunting, left ventricular outflow tract (LVOT) gradient, morbidity, and mortality. Results: Fifteen patients were identified. The average age at operation was 205 days, with mean follow-up time at 1, 364 days. Echocardiograms revealed the following: 12 (80%) patients showed either improved or stable left AV valve performance remaining at "mild" or less insufficiency, while two (13%) declined from "none" to mild and one (7%) from mild to "severe, " which required reoperation. There was no residual shunting or LVOT obstruction at follow-up. The single (7%) reoperation was performed after three years due to left AV valve zone of apposition dehiscence. No permanent pacemakers were needed, and no deaths were reported. Conclusion: Our initial experience with CorMatrix in the repair of CAVSD in children has resulted in good initial and midterm outcomes. The CorMatrix patch remained stable through midterm follow-up, thus may be efficacious for use in CAVSD repair.